Efficiency and Electrical Power Consumption of Prototype-2 Gasification Stove Fueled by Used Cooking Oil - Purwandito Tulus Asmoro; Dani Usman; Feri Siswoyo Hadisantoso; Dwi Nurcahyo; Gimas Sahrul Sopanji (Universitas Muhammadiyah Sidoarjo, 2025)
Abstract. Currently, society and the business still rely on 3 kg and 12 kg LPG gas stoves for cooking. And the supply of LPG in Indonesia is 6.7 million tons, or about 77%; it is still imported from abroad. On the other hand, used cooking oil (Used Cooking Oil/UCO) produced in Indonesia is around 1.2 million kiloliters per year, which proves that Indonesia has a fairly abundant supply of used cooking oil. This used cooking oil, if still used for frying, can be harmful to health, and if disposed of in the environment, will pollute water and soil. Therefore, an innovation arose to create a gasification stove by utilizing waste-used cooking oil that is no longer used as fuel for the stove as a form of appropriate technology that is sourced from renewable energy that is environmentally friendly. This study aims to analyze the efficiency of used cooking oil stoves using the Water Boiling Test (WBT) method, where testing and analysis were carried out using 3 samples of 1 liter of water volume. The test and analysis results showed that the average thermal efficiency was 54.4%, exceeding the minimum requirement of 50%, according to the SNI 8660:2018 standard. The average Fuel Consumption Rate (FCR) value was 0.44 liters/hour, and the average input power (Pin) was 3.58 kW, exceeding the average input power for LPG gas stoves of 2.37 kW. Meanwhile, the electrical power required to operate the stove was 430.1 Watts.